Water Recharging in Wells due to Water Harvesting Structures in Saurashtra and Kuchchha Region of Gujarat A Case Study - Vhora, P.H. (Journal of Soil and Water Conservation, 2022)
Climatic aberration in Saurashtra and Kuchchha Region of Gujarat and poor irrigation facility impede taking up assured and profitable agriculture. In such situation water harvesting specialy through nala plugging help increase Soil moisture and promote recharge to ground water. The case study demonstrated the extent such works could raise water table of wells through direct percolation as well as through lateral movement of water through soil body.